Strengthening Deep Learning: Developing an Ethnomathematics–Collaborative Augmented Reality (ME-CAR) Module to Optimize Numeracy Skills and Self-Regulated Learning - Anwar, Syahrul; Rizal Umami, Moh. (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2025)
Indonesian junior high school students’ persistent low numeracy and limited autonomy necessitate culturally grounded, technology-enhanced learning media. This study developed an Ethnomathematics–Collaborative Augmented Reality Module (ME-CAR) using Educational Design Research with the ADDIE model. The module underwent expert validation (I-CVI ; S-CVI ), small-scale practicality testing (), and large-scale testing (), all rated excellent. Effectiveness was examined through a quasi-experimental pretest–posttest control-group design (experimental ; control ). The experimental group’s numeracy improved significantly () compared to the control (). ANCOVA confirmed a strong treatment effect (). Reliable instruments () supported findings. By integrating ethnomathematics, collaborative AR, and self-regulated learning, ME-CAR uniquely enhances numeracy, autonomy, and contextualized understanding of three-dimensional geometry, contributing a novel digital solution in mathematics education.